Popcorn lung: reflect on implications of vaping - Long, Chiau Ming *; Ser, Hooi Leng *; Look, Keyun; Amar, Daud Iskandar Abdullah *; Elil, Renganathan * (New Straits Times Press (M) Bhd., 2023)
THE prevalence of vaping among teenagers in Malaysia rose from 9.8 per cent in 2017 to 14.9 per cent in 2022.